Suicide and Accidental Death Among Women With Primary Ovarian Cancer: A Population-Based Study - Ying Chen; Kaixu Yu; Jiaqiang Xiong; Jinjin Zhang; Su Zhou; Jun Dai; Meng Wu; Shixuan Wang (Frontiers in Medicine, 2022)
BackgroundWomen with ovarian cancer had the highest suicidal rate among all patients with gynecological malignancies, but no large studies about suicide and accidental death for women with ovarian cancers in detail were conducted. We aimed to determine the relative risk of suicide and accidental death among patients with ovarian cancer to that of the general population, and to identify risk factors associated with suicide and accidental death.MethodsData are from the SEER (surveillance, epidemiology, and end results) cancer registry of women diagnosed with ovarian cancer data from 18 registries for the years 1973–2016. The study population comprised 149,204 patients after inclusion and exclusion criteria were applied. Standardized mortality ratios (SMRs) were calculated and Fine-Gray models were fitted to identify risk factors associated with suicidal and accidental death among cancer patients, with stratifications on demographic and tumor-related characteristics.ResultsWomen with ovarian cancer had a higher risk of suicide and accidental death than the cancer-free group [SMR = 1.86; 95% CI (1.54–2.25) and SMR = 1.54; 95% CI (1.39–1.71)]. Subgroup analysis indicated that only patients with type II epithelial ovarian cancer [SMR = 2.31; 95% CI (1.83–2.91)] had an increased risk of suicide, and those with type I and type II epithelial ovarian cancer [SMR = 1.65; 95% CI (1.39–1.97) and SMR = 1.49; 95% CI (1.30–1.70)] were at a higher risk of accidental death. Patients with ovarian cancer who were younger, white, diagnosed with high-grade, non-metastatic cancer and pelvic exenteration were at a higher risk of suicide. The advanced age, earlier year of diagnosis, and non-metastatic cancer were associated with a higher risk of accidental death. Additionally, pelvic exenteration increased the risk of suicide but not the risk of accidental death among women with primary ovarian cancer.ConclusionsWomen with ovarian cancer had a higher risk of suicide and accidental death compared with the general population. The findings suggested that clinicians should identify high-risk subgroups of ovarian cancer patients for suicide and accidental death as early as possible, with appropriate prevention strategies.